Agile engagement : how to drive lasting results by cultivating a flexible, responsive, and collaborative culture - Jaramillo, Santiago, 1989- (Wiley, 2016)
Achieve unprecedented business value by fostering true employee engagement Many organizations fail to realize and harness the power of their most valuable asset-their employees. Though they can be developed into a true competitive advantage, engagement isn't attainable if the employee isn't invested in the company's overall success. Agile Engagement offers business leaders a concrete strategy for building, maintaining, and utilizing employee engagement to achieve the highest level of business success. The key' Employees must feel like they are a part of their company's culture instead of having it handed down to them. Stories of failed employee engagement initiatives abound, and they all have one thing in common: they begin from the premise of "initiative" rather than "employee." True engagement occurs when an employee's heart and mind are activated in a way that leads to their motivation and commitment to positively impact the company's goals and vision. This book shows you how to create an environment that stresses a culture of unity at all levels by showing you how to: -Create a clear, compelling vision and corresponding engagement strategy through the Engagement Canvas -Communicate your unique culture strategy throughout all levels of your company -Foster grassroots, employee-led engagement initiatives -Improve engagement continuously with the Emplify Score tool Agile Engagement provides a deeper look into real engagement, helping you foster a work environment that's rewarded with unsurpassed productivity, innovation, and competitive advantage, as well as employees who feel valued, respected, and heard.